PENETAPAN KADAR PROTEIN TEMPE JAGUNG (Zea mays L.) DENGAN KOMBINASI KEDELAI (Glycine max (L.) Merill) SECARA SPEKTROFOTOMETRI SINAR TAMPAK - Siti Jubaidah; Henny Nurhasnawati; Heri Wijaya (Jurnal Ilmiah Manuntung, 2016)
Indonesian is still very dependent of soybean imports, so as to reduce the use of soybean need to find substitute materials in the manufacture of soybean. Corn can be an option because apart from being a source of carbohydrates, corn is also an important source of protein in the menu society in Indonesia. The purpose of this study to determine the levels of soybean protein maize (Zea mays) with a combination of soybean (Glycine max (L.) Merrill) with visible of spectrophotometry. The research design uses a comparison of corn: soybean as follows: P1 = 80: 20; P2 = 70: 30; P3 = 50: 50; P4 = 30: 70 and P5 = 20: 80. The results of this study indicate that P1 has a protein content of 6.7%, P2 = 8.06% = 10.76% P3, P4 and P5 = 13.46% = 14.8%. The greater the concentration ratio of soy protein obtained even greater. In organoleptic quality in soybean corn combination has the texture a little hard to hard, has no smell until the typical aroma smelled soybean, flat white to brown of white